Blessed are the peacemakers? Framing crusade and diplomacy with Muslims in Latin Christendom, c.1095-1300 - Moynihan, TS (2022)
Diplomacy and holy war are generally understood as not only incongruous, but opposing concepts. Those inspired to take up arms in the name of their faith, such as the Latin Christians who endeavoured upon the capture of Jerusalem between the late-eleventh and thirteenth centuries, are often considered incapable of the rational compromises required by any effective diplomacy. This assumption, however, fails to adequately explain the prevalence and frequency of diplomatic encounters between those who led crusade campaigns to the East and their Muslim counterparts. While an openness to negotiations and treaties might be expected of the Latin Christians who chose to settle in the East, this thesis seeks to establish how diplomacy was viewed by those who took the cross and travelled great distances in order to capture the holy city of Jerusalem, as well as by those who never left the Latin West but whose chronicles, letters and other writings provided the crusading movement with its language and ideals. If these men saw no place for negotiation in holy war, then why did it occur so often? Where did diplomacy stand in the conceptual framework of crusading? Through a wide-ranging analysis of normative texts and contemporary sources, this thesis establishes a more firm foundation for the study of diplomacy between crusaders and Muslim leaders. Forgoing any assumptions that diplomacy and holy war must have been seen as incompatible, it provides new frameworks for understanding the relationship between the two concepts. It argues that negotiation was not an action which stood outside the normative boundaries of holy war in the twelfth and thirteenth centuries, but was rather an accepted component of a broader war effort, which was to be judged upon its results. Significantly, many of the same ideological, legal, and cultural frameworks which celebrated and encouraged religious violence also supported diplomacy and negotiation. A better understanding of how these concepts were entwined and understood in the period reveals how diplomacy should be seen as a core aspect of the crusading movement, in both practice and theory.